Effect of Field Of View on Detection of External Root Resorption in Cone-Beam Computed Tomography - Safi, Yaser; Ghaedsharaf, Sahar; Aziz, Alireza; Hosseinpour, Sepanta; Mortazavi, Hamed (Iranian Endodontic Journal, 2017)
Introduction: Conventional methods for diagnosis of external root resorption (ERR) are based on clinical findings and x-ray observations which are not appropriate for early diagnosis. The present study assessed the effect of different sizes and field of views (FOVs) in the diagnosis of simulated external root resorption by cone-beam computed tomography (CBCT). Methods and Materials: In this diagnostic in vitro trial, 100 human extracted mandibular central incisors were collected and marked in 3 apical, middle and coronal areas. Cavities with different sizes were created in buccal and lingual surfaces of each area. Following this procedure, CBCT images were taken in 2 different 6 × 6 cm and 12 × 8 cm FOVs with the same voxel size of 0.2 mm. Absence or presence of cavities in CBCT images were assigned by 3 radiologists and compared with gold standard results which were obtained by measurement of the size of cavities using a digital caliper. Sensitivity and specificity values, positive predictive value (PPV) and negative predictive value (NPV), AZ value and Kappa values were calculated and reported. Results: Amounts of sensitivity in 6 × 6 cm FOV with voxel size of 0.2 mm for small, medium and large cavities were 95.93%, 96.03% and 97.1%, respectively. Amounts of sensitivity in 12 × 8cm FOV with the same voxel size for small, medium and large cavities were noted as 94.4%, 96.03% and 98.5%, respectively. However, specificity in FOV of 6 × 6 cm and FOV of 12 × 8 cm was calculated as 93.03% and 90.83%, respectively. Conclusion: Both used FOVs show nearly same performances in the case of detection of ERR; therefore, smaller FOV should be preferably used for detection of ERR in order to decrease the amount of imposed radiation dose given to patients. Keywords: Cone-Beam Computed Tomography; External Root Resorption; Field of View